2014
DOI: 10.3390/rs61110913
|View full text |Cite
|
Sign up to set email alerts
|

Emissivity Measurements of Foam-Covered Water Surface at L-Band for Low Water Temperatures

Abstract: For a foam-covered sea surface, it is difficult to retrieve sea surface salinity (SSS) with L-band brightness temperature (1.4 GHz) because of the effect of a foam layer with wind speeds stronger than 7 m/s, especially at low sea surface temperature (SST). With foam-controlled experiments, emissivities of a foam-covered water surface at low SST (−1.4 °C to 1.7 °C) are measured for varying SSS, foam thickness, incidence angle, and polarization. Furthermore, a theoretical model of emissivity is introduced by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
(66 reference statements)
2
1
0
Order By: Relevance
“…Anguelova (2008) theoretically ranked the suitability of these models to sea foam as: 1) Refractive model; 2) Looyenga model; 3) Polder-van Santen model; 4) Maxwell-Garnett model. A recent in-situ study (Wei et al, 2014) also confirmed that the refractive model better fits the emissivity measurements of foam-covered water surface at L-Band than the other models.…”
Section: Foam Emissivity From Incoherent Approachsupporting
confidence: 71%
See 1 more Smart Citation
“…Anguelova (2008) theoretically ranked the suitability of these models to sea foam as: 1) Refractive model; 2) Looyenga model; 3) Polder-van Santen model; 4) Maxwell-Garnett model. A recent in-situ study (Wei et al, 2014) also confirmed that the refractive model better fits the emissivity measurements of foam-covered water surface at L-Band than the other models.…”
Section: Foam Emissivity From Incoherent Approachsupporting
confidence: 71%
“…New theoretical studies of foam dielectric and radiative properties (Anguelova, 2008;Anguelova & Gaiser, 2013) use high void fraction values, usually v af N 90%. Such a high void fraction up to 0.95-0.99 provides the high, black-body-like emissivity for foamcovered surfaces that has been observed in in-situ experiments (Rose , 2002;Wei et al, 2014) and under laboratory conditions (Blenkinsopp & Chaplin, 2007;Ryu & Chang, 2008). The foam void fraction v af from SMOS TB are higher than that from the FROG 2003 field experiment (Camps et al, 2005) (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…This phenomenon agrees with the general trend of the theoretical effect of H-V polarisations at different incidence angles (Wei et al, 2014).…”
Section: Smos Datasupporting
confidence: 80%